2015
DOI: 10.1002/ijc.29475
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum and maternal cancer risk, a scandinavian nested case‐control study

Abstract: Reproductive factors have been shown to influence cancer risk. Several pathological conditions during pregnancy have also been associated with subsequent altered cancer risk in the mother. Hyperemesis gravidarum (hyperemesis) is an early pregnancy condition characterized by severe nausea and vomiting resulting in weight loss and metabolic disturbances. Studies have reported associations between hyperemesis and cancer, but results are inconsistent. In this nested case-control study we linked the population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
13
1
2
Order By: Relevance
“…We found, however, that women who had experienced hyperemesis during any of their pregnancies had similar breast cancer risk overall to women who did not, at both premenopausal and postmenopausal ages. This is contrary to results from a case–control study reporting a positive association after a recent hyperemetic pregnancy in premenopausal women and one reporting inverse associations, but accords with several other studies . The prevalence of reported hyperemesis in our study (28.7%) was much higher than in surveys of prevalence of this condition (e.g., 0.3–3%).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…We found, however, that women who had experienced hyperemesis during any of their pregnancies had similar breast cancer risk overall to women who did not, at both premenopausal and postmenopausal ages. This is contrary to results from a case–control study reporting a positive association after a recent hyperemetic pregnancy in premenopausal women and one reporting inverse associations, but accords with several other studies . The prevalence of reported hyperemesis in our study (28.7%) was much higher than in surveys of prevalence of this condition (e.g., 0.3–3%).…”
Section: Discussioncontrasting
confidence: 67%
“…This is contrary to results from a case-control study reporting a positive association after a recent hyperemetic pregnancy in premenopausal women 24 and one reporting inverse associations, 14 but accords with several other studies. 13,[20][21][22][23] The prevalence of reported hyperemesis in our study (28.7%) was much higher than in surveys of prevalence HR: hazard ratio; CI: confidence interval. *Reference group 5 never hyperemesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The latter is based on lower insulin sensitivity. There is no evidence for an increased cancer risk, although maternal thyroid cancer was positively associated with HG [176][177][178].…”
Section: Overlap Of Symptom Complexesmentioning
confidence: 77%
“…Some studies have reported an association between HG and risk of autoimmune disease later in life 23, 24. A recent study investigating cancer risk after HG exposure reported an inverse association between HG and overall cancer risk 25. The association between HG and mental health, both as a risk factor and as a consequence of HG, has been disputed 15, 26.…”
Section: Introductionmentioning
confidence: 99%